2017
DOI: 10.1590/s0103-40142017.31890013
|View full text |Cite
|
Sign up to set email alerts
|

Crise e perspectivas para a economia brasileira

Abstract: Resumo Este artigo analisou a performance da economia brasileira no período 2003-2016, focando em particular na desaceleração econômica recente e recessão que a seguiu. Nossa análise mostra que houve tanto problemas de coordenação na política macroeconômica que tornou políticas anticíclicas pouco eficazes no período 2011-2014 (assim como no caso das políticas contracionistas em 2015) quanto problemas relacionados a choques exógenos. O artigo avalia e sugere algumas políticas econômicas - de curto e de longo pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 7 publications
0
33
0
25
Order By: Relevance
“…Recently, the Food and Agriculture Organization of the United Nations (FAO) reported that undernourishment at a global level, after years of decline, increased from 2015 to 2016 due to the economic and political crises that occurred in many developing countries 8 . The impact of economic downturns on food security suggests a threat to food security in Brazil, as since 2014 the country faces a major economic crisis along with political instability 26,27,28 . As a result, in 2016 there was a presidential impeachment in Brazil, which along with many revelations of corruption compromised the political stability of the country 10,27 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Food and Agriculture Organization of the United Nations (FAO) reported that undernourishment at a global level, after years of decline, increased from 2015 to 2016 due to the economic and political crises that occurred in many developing countries 8 . The impact of economic downturns on food security suggests a threat to food security in Brazil, as since 2014 the country faces a major economic crisis along with political instability 26,27,28 . As a result, in 2016 there was a presidential impeachment in Brazil, which along with many revelations of corruption compromised the political stability of the country 10,27 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in 2016 there was a presidential impeachment in Brazil, which along with many revelations of corruption compromised the political stability of the country 10,27 . This crisis lead to the worsening of many social indicators, such as income and unemployment, which affected 12% of the population in 2016 15,26,27 . Inflation led to increases in national food prices, mostly affecting staple foods (rice, beans), vegetables, fruits and meat 15,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, as organizações foram obrigadas a se reinventar, à medida que eram expostas à políticas intervencionistas. Esses elementos são passíveis de estímulo à pesquisas sobre evidenciação contábil, visto que o cenário das organizações estava imerso em insegurança política e econômica (Formiga, Barros, Cezário, & Scherer, 2017;Paula & Pires, 2017).…”
Section: Anounclassified
“…The municipalities' own resources were and have been such important factors to the "fiscal municipalism" in Brazil that in recent years, it is possible to identify an interesting aspect about the direct collection of local governments: the continuing tendency of an expanding tax burden even with the economic crisis that took hold of the country from 2014 [17]. The country's total tax burden has been showing a pattern of contraction since 2011, leading Ribeiro [18] to point out the existence of a structural break in Brazilian tax elasticity with respect to economic performance from the subprime crisis of 2008.…”
Section: Historical Evolution Of Municipal Taxationmentioning
confidence: 99%